Comparison Between Head Village and Midwife as Health Educator of Maternal and Child Health (MCH) in Increasing Husband’s Knowledge of MCH in the Village : Perbandingan Antara Kepala Desa dan Bidan Sebagai Penyuluh Kesehatan Ibu dan Anak (KIA) dalam Meningkatkan Pengetahuan Suami Tentang KIA di Desa - Afrona Elisabet Lelan Takaeb; Helga Ndun; Indriati Tedju Hinga (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2022)
Background: Partnership with local head villages to deliver maternal and child health (MCH) education is considered necessary, as the availability of health professional is limited in rural remote area. While the head villages could be viewed as credible, they have rarely been involved as a health communicator in their villages. Objective: This study aimed to analyze the difference of the knowledge level of the heads of family (husband) after attending MCH education delivered by the head village and midwife. Methods: The research method applied was quasi experiment with non-equivalent control design conducted in two remote villages in Timor Tengah Selatan District. The population was all heads of the family (husband) living in two selected villages, with a total of 920. The sample of 60 men was selected purposively. The experiment and control group consisted of 25 and 35 men, respectively. Data were analyzed using t-test dependent and t-test independent. Results: The result showed that 1. Both MCH education delivered by the head village and midwife increased the level of knowledge of husband with the value of (Ï) 0,00 <(É‘) 0,05; 2. The head village and midwife were equally effective as communicators in increasing the knowledge level of husbands about MCH with the value of (Ï) 0,245 >É‘ (0,05). Conclusion: Both the village head and the midwife can be educators in increasing the knowledge of MCH among husbands. Thus, the village head could also be empowered as an alternative MCH communicator.